2021
DOI: 10.1111/nep.13816
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin based non‐rifampicin anti‐tuberculous therapy: An effective alternative in renal transplant recipients in resource limited setting

Abstract: Introduction Rifampicin is one of the most effective components of anti‐tuberculous therapy (ATT). Since rifampicin is a hepatic enzyme (CYP3A4) inducer, in a post‐renal transplant recipient, the dose of calcineurin inhibitors needs to be up‐regulated and frequently monitored. In resource‐limited (low‐ and lower‐middle‐income countries) setting this is not always feasible. Therefore, we evaluated a non‐rifampicin‐based ATT using levofloxacin in kidney transplant recipients. Methods We retrospectively studied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In another study, Gupta and colleagues studied renal transplant patients who received rifampicin-sparing treatment. 26 The study showed favorable responses in 60 of 67 (93.7%) patients after a median treatment time of 12 months, and one patient experienced recurrence.…”
Section: Discussionmentioning
confidence: 80%
“…In another study, Gupta and colleagues studied renal transplant patients who received rifampicin-sparing treatment. 26 The study showed favorable responses in 60 of 67 (93.7%) patients after a median treatment time of 12 months, and one patient experienced recurrence.…”
Section: Discussionmentioning
confidence: 80%
“…21 Fluoroquinolonebased regimens have been used in solid organ transplant recipients diagnosed with TB with excellent results. [20][21][22] Although one of our patients received ofloxacin, the newer generation fluoroquinolones (moxifloxacin, gatifloxacin, and levofloxacin) have better efficacy 23,24 in the treatment of TB and hence should be preferred agents for transplant recipients with TB. We used a 4-drug rifampicin containing intensive phase ATT pre-transplantation with a fluoroquinolone-based continuation phase ATT post-transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of observational studies from SA have shown the efficacy of a regime in which RIF is replaced with fluoroquinolone. 11,22,30 If possible, patients should receive the standard 4-drug treatment (including RIF); however, RIF is a potent inducer of cytochrome A 450 and can lead to a marked reduction in the levels of CNIs, thus increasing the risk of acute rejections in 30% of cases and graft loss in 20%. 14 The interaction is sometimes unpredictable, and it can reduce the CNI levels by 2 to 5 times.…”
Section: Treatment Of Tb After Transplantmentioning
confidence: 99%
“…A recent study from India used a levofloxacin-based regimen (without RIF) in their patients after transplant, and they were successful in full remission in >90% of patients. 22…”
Section: Endemicbacterial Infectionsmentioning
confidence: 99%